Student-centered curriculum design and evaluation in logistics management - Sajad Fayezi (Logistics, 2022)
Background: In this essay, we address an important issue in the logistics education discourse relating to student-centered curriculum design and evaluation. Methods: We adopt an integrative approach based on conceptual development and guided by constructive alignment. Results: We apply and elaborate our conceptual framework using a case of a teaching plan in logistics management. We also propose an evaluation strategy for our teaching plan in the form of a template. Conclusions: Our essay contributes to the logistics education discourse by using learning theories and developing curriculum design and evaluation guidelines that can be replicated by other educators.
Keywords: 650; constructive alignment; curriculum design; curriculum evaluation; logistics management